A note on asymptotic helix and quantum mechanical structure - Partha Guha (International Journal of Mathematics and Mathematical Sciences)
Using the formulation of a moving curve, we demonstrate that an asymptotic helix goes over to the linear time-dependent Schrödinger equation as shown by Dmitriyev (2002).